FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PROPERTI RUMAH TINGGAL PADA KOMPLEK PERUMAHAN DI KOTA MEDAN SUMATERA UTARA - , Muhammad Arliyan, S.E., Dra. Wahyu Hidayati, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research to examine the factors that affect the value of residential property in the residential complex in the city of Medan, North Sumatra. The data used in this study of secondary data derived from home advertising info tabloid published once a month locally in Medan, the data used amounted to 42 units of observation, methods of sampling in this research using purposive sampling method, which can be interpreted as sample is carefully selected so that relevant to the study design, because the researchers wanted to know to what extent the independent variables on the dependent variable of this study affect the value of residential property that has value â¥ 1.000.000.000. Dependent variable used is the value of the property, while his independent variables include the land area, building area, distance to the center of economic activity as well as the width of the street front location. Analysis tool used is multiple regression (Multiple Regression) because in this research using more than one independent variable with the methods (Ordinary Least Squares) OLS. The results showed that all independent variables affect the value of residential property. Variable land area, building area, the width of the front street location, has positive and significant impact on residential property values. Conversely, the distance to the center of economic activity and a significant negative effect on the value of residential property.